(untitled) (Al-Academy, 2020)
The Child’s theatre was and still is the most investing art for masks of all kinds (partial and total) for suspense, aesthetic and artistic purposes that meet the requirements of those performances. Here the actor’s performance is associated with two tools, i.e. the body and the mask, where it has become a must to search for the performance transformations required in order to achieve the highest level of the right performance through this dualism. This urged the researcher to address this problem. Thus, the researcher has put forward an objective to identify the transformations of the character’s performance between the body and the mask in the child’s theatre shows. The research consists of a methodological framework and a theoretical framework, in which the dualisms of the body and mask, sound and motion, function and significance, are addressed. Then the researcher formulated indicators used as standards to analyze a sample consistent with his research limits. Finally, the research ends with results and conclusions. The most significant of these results is the direct connection between the voice and motion performance of the actor with the nature of the mask that he is wearing and what it signifies in order to create the perfection between the shape of the mask and the structure of the voice and motion performance of the character. The study has concluded with a list of the resources and an abstract in English